International Trade and The Impact of Information and Communications Technology (ICT) Access and Use: A Study of Southeast Asian Nations - Manickam, Hemleen Soosai; Idris, Sidah; Nipo, Debbra Toria (UUM Press, 2021)
Continuous evolution of technologies and globalization have enabled international trade to be done via borderless selling and buying activities. This research underlines the relevance of ICT in impacting international trade in early member countries of ASEAN (Malaysia, Thailand, Philippines, Singapore and Thailand), in line with the Industry 4.0 Revolution. This study employs the examination of panel data to investigate the access to and use of ICT towards international trade. In accordance to that, the export and import of products and services are used to measure international trade. Mobile cellular subscriptions, Internet users, fixed broadband subscriptions, and fixed telephone subscriptions are all used to quantify ICT access and usage. In addition, control variables include foreign direct investment (FDI), research and development (R&D), real exchange rate, and also inflation. Government policy as the moderating variable on ICT against international trade is also discovered. As a result, this study takes a 10-year period to collect numerical data and analyse it using statistics and mathematical methodologies. Findings from the study are expected to show whether ICT has significant influence in promoting trade activities among the selected ASEAN member countries. Additionally, the study is also expected to bring some clarity on the potential role of government policy in moderating the impacts of ICT towards international trade. Overall, findings from the study would provide some insights to governments and policy makers on the crucial need to adopt ICT in daily operations to sustain trade activities. Future research direction may include expanding the scope of the countries and investigating the impacts of other types of ICT such as ICT skills and adoption.